BIOMEKANIKA DALAM SHOOTING, PASSING, DAN DRIBBLING BOLA BASKET - Hardiansyah Pratomo, Edvan; Gumilar, Agus; Darajat Kusumah Negara, Jajat; Mudjianto, Sufyar (Jayabama: Jurnal Peminat Olahraga, 2025)
This study aims to analyze the application of biomechanical principles in three basic basketball skills, namely shooting, passing, and dribbling. Biomechanics as a branch of science that studies human body movement provides important insights into how players can improve efficiency, accuracy, and consistency in performing these movements. This study uses a literature approach to review various relevant previous studies. The findings show that in shooting, the optimal ball release angle ranges from 45–55 degrees with the support of strength from the elbow extensor and wrist flexor muscles. Body stability, especially core muscles, also contributes greatly to shooting accuracy, especially in techniques such as jump shots and fadeaways. In passing, biomechanics highlights the importance of coordination between shoulder, arm, and hand muscles to produce fast and accurate passes. Variations in passing techniques, such as chest pass, bounce pass, and overhead pass, require different angle and strength settings to ensure effectiveness in the game. Meanwhile, in dribbling, the angle of the hand push, ball speed, and rhythm are key factors in maintaining ball control. Effective dribbling also requires coordination between the eyes, hands, and feet, as well as body stability to support rapid changes of direction without losing control of the ball. Further discussion highlights how the application of biomechanics in training can help players gain a deeper understanding of their movements, reduce the risk of injury, and improve overall performance. This study provides a strong theoretical contribution to the development of biomechanics-based basketball training strategies. By integrating these findings into training programs, coaches and players can improve the effectiveness and efficiency of their game, creating more competitive players at both the amateur and professional levels. This study also encourages further exploration of the application of biomechanics to other aspects of sports to expand the understanding and impact of biomechanics in the world of sport.